2011
DOI: 10.1186/1471-2407-11-397
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant upregulation of 14-3-3ơ expression serves as an inferior prognostic biomarker for gastric cancer

Abstract: Background14-3-3ơ is an intracellular, phosphoserine binding protein and proposed to be involved in tumorigenesis. However, the expression dynamics of 14-3-3ơ and its clinicopathological/prognostic significance in human tumors are still controversial.MethodsThe method of immunohistochemistry (IHC) and Western blot were utilized to examine the protein expression of 14-3-3ơ in gastric cancer and paired normal adjacent gastric mucosal tissues. Receive operating characteristic (ROC) curve analysis was employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…The genes were associated with cell adhesion and regulation of cell proliferation (Table ). The genes for fibroblast growth factor binding protein 1 ( FGFBP1 ), stratifin ( SFN ), melanoma inhibitory activity ( MIA ), Muc4 ( MUC4 ), macrophage stimulating 1 receptor ( MST1R ), and catenin (cadherin‐associated protein) beta 1 ( CTNNB1 ) are reportedly involved in cancer progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes were associated with cell adhesion and regulation of cell proliferation (Table ). The genes for fibroblast growth factor binding protein 1 ( FGFBP1 ), stratifin ( SFN ), melanoma inhibitory activity ( MIA ), Muc4 ( MUC4 ), macrophage stimulating 1 receptor ( MST1R ), and catenin (cadherin‐associated protein) beta 1 ( CTNNB1 ) are reportedly involved in cancer progression.…”
Section: Resultsmentioning
confidence: 99%
“…cDNA microarrays of fresh gastric cancer tissue used in our study revealed differential expression of genes related to metastasis and invasion in tissues with high (≥25%) and low (<25%) levels of Muc5AC expression. Among the altered genes, FGFBP1 , SFN , MIA , MUC4 , MST1R and CTNNB1 are reportedly involved in cancer progression. These results indicate the possible genes underlying Muc5AC‐associated cancer invasion mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemistry (IHC) assay was performed as previously described [30]. The TMAs slides were deparaffinized in xylene, rehydrated through graded alcohol, and subsequently immersed in 3% hydrogen peroxide for 10 min to block endogenous peroxidase activity.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, molecular pathology may be helpful to understand the disease pathogenesis and provide useful prognostic molecular markers. Potential biologic prognostic markers include overexpression of 14-3-3o, VEGF, mesothelin, EGF receptor, and elevated plasma level of osteopontin (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%